Kajian Peran Petugas Apron Movement Control (Amc) Dalam Menjalankan Prinsip 3S+1C Di Wilayah Airside Bandar Udara Internasional Sentani Jayapura, Papua - Astri Borean (Jurnal Mahasiswa: Jurnal Ilmiah Penalaran dan Penelitian Mahasiswa, 2024)
The Apron Movement Control (AMC) Unit is a unit that is responsible for regulations, monitoring aircraft movements, vehicle traffic, people and goods as well as cleanliness in airside areas, recording flight data so that aviation security and safety can be achieved. In carrying out the duties and responsibilities of the AMC unit, it is based on 3S+1C (Safety, Security, Service and Compliance). As a measure of success in the role of duties and responsibilities, the AMC unit must optimize the 3S+1C principles. Safety, Security, Service and Compliance are the principles of the AMC unit to create safety, security and aviation services without compromising all the regulations that have been established. This research aims to find out the role of AMC officers in optimizing the 3S+1C principles in the airside area and the obstacles for AMC officers to achieve the 3S+1C principles at Sentani Jayapura International Airport, Papua. This research uses a descriptive qualitative approach. The data used are primary and secondary data. Primary data was obtained from observations and interviews, while secondary data came from SOPs, photos and regulations related to the problems studied. The data analysis techniques used are data reduction, data presentation and drawing conclusions. To test the validity of the data, triangulation techniques were used. The results of this research show that the Apron Movement Control (AMC) officers at Sentani Jayapura International Airport, Papua have optimized the 3S+1C principles in accordance with existing Standard Operating Procedures. Starting from passenger services which include Aviobridge services, Slot Time ETA (Estimated Time Of Arrival) and ETD (Estimated Time Of Departure) and Plotting Parking Stand. AMC officers have also carried out their responsibilities for safety in the Airside Area, identifying Hazards, monitoring every movement at the Airside, carrying out cleanliness and order inspections at the Airside. AMC officers have implemented Compliance Principles or compliance with the rules that apply in the Airside Area, this is in the form of implementing SOPs for officers who carry out all work in the Airside Area. AMC officers have the obligation and responsibility to take action against officers or parties who violate the rules in the Airside Area, especially regarding handling FOD (Foreign Object Debris). Obstacles for AMC officers to achieve the 3S+1C principle at Sentani Jayapura International Airport include damage to security facilities in the airport area such as apron guardrails which do not have barbed wire, holes and holes that allow animals to enter the airside area, thereby endangering safety and security. security and lack of monitoring facilities such as CCTV for remote monitoring. Then, in the AMC supervision area, we often find officers or parties who do not use Airport Passes (Legality/Permit Signs) and safety equipment in the form of vests during operational hours and lack of awareness of officers or other parties in handling FOD, such as fuel spills in the Airside Area. The Sentani Jayapura International Airport AMC unit also has problems in terms of a shortage of personnel during working hours which means personnel have to do double duty so that there are often delays when carrying out Aviobridge services and routine FOD inspections, this also has quite a significant impact on operational times.